Hubungan Pengetahuan Dan Sikap Bidan Desa Terhadap Keterampilan Pencegahan Hipotermia Pada Bayi Berat Lahir Rendah Dl Kabupaten Purworejo - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Low birth weight babies have high risk of perinatal mortality, 9.4 times higher than the normal birth weight. In developing countries, one of which is Indonesia, approximately 19 million babies are low birth weight with the incident number around 11 - 31%. There are 471 low birth weight babies out of 10.198 births until July 2002 in Purworejo regency. Fourty percents out of 80% of neonatal mortality in low birth weight babies is caused by hypothermia. In Nepali Hospital 80% of newborn babies have hypothermia, therefore, a serious and intensive treatment is necessary that mortality risk of hypothermia can be prevented. Rural midwives as front-line medical officials who directly cope with labour process are expected to be skillful and have positive knowledge and attitude toward low birth weight babies cases, especially in hypothermia prevention. This study was aimed to find out the relationship between knowledge and attitude of rural midwives to hypothermia preventing skills to low birth weight babies. This was an observational analitic study using a cross-sectional approach. This study was held in Purworejo regency covering five districs, Bener, Kutoarjo, Bagelen, Butuh and Gebang. The subjects were all rural midwives who have ever helped labour process of low birth weight babies. The samples were obtained by using total sampling of 53 rural midwives. Correlation statistic test was used to analyze the correlation between knowledge, attitude, and skills. Multi regression test was used to analyze the correlation between age, work period, and skills. The study showed that there was significant correlations (p